2016
DOI: 10.15171/joddd.2016.043
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and perceived stress in Australian dental undergraduates: Preliminary outcomes

Abstract: Background. Dental students have reported a high prevalence of psychological stress and the causes are associated with the challenging dental environmental and demographic factors. This study aimed to conduct a preliminary investigation on dental students’ stress status, using a sample of first-to-third-year Bachelor of Dental Surgery students in an Australian university. Special interests included causes of dental environmental stress and access to help services.Methods. A sample of 145 students was surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
2
11
1
1
Order By: Relevance
“…In particular, both years 2 and years 3 Australian DHDTS reported criticism about academic or clinical work as a high source of stress (which was similar to that reported by DHDTS in the SA study), with approachability of staff an additional high source of stress to the year 3 students (Table ). These were also the same sources of stress reported by third‐year dental students in a recent Australian study . In this study, the authors attributed the reported stressors to the increased contact time with staff in the clinical setting, and frustration for students to try and adopt differing techniques advised by different clinical staff.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, both years 2 and years 3 Australian DHDTS reported criticism about academic or clinical work as a high source of stress (which was similar to that reported by DHDTS in the SA study), with approachability of staff an additional high source of stress to the year 3 students (Table ). These were also the same sources of stress reported by third‐year dental students in a recent Australian study . In this study, the authors attributed the reported stressors to the increased contact time with staff in the clinical setting, and frustration for students to try and adopt differing techniques advised by different clinical staff.…”
Section: Discussionsupporting
confidence: 71%
“…These were also the same sources of stress reported by third-year dental students in a recent Australian study. 24 In this study, the authors attributed the reported stressors to the increased contact time with staff in the clinical setting, and frustration for students to try and adopt differing techniques advised by different clinical staff. The reasons for the differences between DHDTS in our study could be explained by the variation of how the curriculum is delivered in the UK and Australia (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…1 Bu araştırmanın bu sonuçları, konu ile ilgili yapılan araştırmaların sonuçları ile paralellik gös-termektedir. [32][33][34] Annenin eğitim düzeyi ile anksiyete, depresyon ilişkisi incelendiğinde, annenin eğitim düzeyi ile STAI-I, STAI-II ve BDI değerleri arasında istatistiksel olarak anlamlı bir şekilde fark bulunmamıştır. Literatüre bakıldığında ise Kaya ve ark.nın çalışmasında da bulgularımızla uyumlu olarak, annenin eğitim düzeyi ile depresif belirti puanları arasında fark olmadığı rapor edilmiştir.…”
Section: Discussionunclassified
“…4,[7][8][9][10] Several studies report that perceived sources of stress vary by year in dental school. [10][11][12] For example, one study found that fourth year and graduating students were less concerned about class workload, clinical training, and failing courses, but more concerned about their professional future, whereas entry-level students were more concerned about time for relaxation. 10 Another study found that second-and thirdyear students reported more stress from transition to clinical training, whereas first-year students reported more stress from difficulty of coursework.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another study found that second-and thirdyear students reported more stress from transition to clinical training, whereas first-year students reported more stress from difficulty of coursework. 11 Dental residents usually have substantial clinical responsibilities along with educational and research requirements. However, to our knowledge, only two previous studies investigated stress among dental residents.…”
Section: Introductionmentioning
confidence: 99%